The influence of heads of department personalities on the selection of grievance handling styles - Daud, Zulkiflee; Yahya, Khulida Kirana; Md Isa, Mohd Faizal; Wan Mohd Noor, Wan Shakizah (Centre for Promoting Ideas (CPI), 2011)
Grievance management is an important topic in the area of industrial relations.Research on grievance management is burgeoning, and yet the understanding of its antecedents and consequences remains rather unclear.This research discusses the styles in handling grievances among heads of department at a telecommunication headquarters and branches located in Peninsular Malaysia and the determinant of personalities in selecting the appropriate styles.It was conducted to achieve two main objectives which are to investigate the styles managers use in handling employee grievances and to examine influence of personalities in choosing style used by the managers in handling grievances.The result of factor analysis reveals that the grievance handling styles used by managers in this study are integrating, compromising and dominating. In general, the study reveals that extra version is negatively and significantly influences the selection of integrating style.Conscientiousness contributes significantly to the prediction of dominating style.Finally, emotional stability is positively and significantly influences compromising style in handling grievances.